Strategi Penerapan Manajemen Mutu, Pengelolaan Risiko, dan Penetapan Harga untuk Meningkatkan Kepuasan dan Loyalitas Pelanggan pada UMKM Roemah Laundry - Rizky Zachi Afriandi; Angelina Laia; Evelyna Faiqah Zahra; Vivi Nila Sari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic development, one of which is through the rapidly growing laundry service sector in Padang City. Roemah Laundry, as an MSME player in the laundry service sector, faces challenges in maintaining service quality and customer loyalty amidst intense competition. This study aims to examine the application of quality management, risk management, and pricing strategies implemented by Roemah Laundry to increase customer satisfaction and loyalty. The methods used include evaluating operational processes, quality control, employee training, as well as analyzing pricing strategies and risk management. The results of this study are expected to provide practical recommendations for Roemah Laundry to improve business effectiveness and serve as a reference for other MSME players in facing competition in the laundry service sector. Additionally, this study contributes to the development of MSME management science, particularly in improving service quality and sustainable business strategies.